2009
DOI: 10.1603/022.038.0111
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Fungal–Plant–Insect Interactions: The Importance of a Community Approach

Abstract: Mycorrhizal fungi and insects are important components of most ecosystems that are likely to interact with one another indirectly through a common host plant. In this paper, we review the literature examining the effects of insects on mycorrhizal fungi and the effects of mycorrhizal fungi on insects and show that both groups of organisms can indirectly and, occasionally directly, influence each other. We explore the mechanisms for these interactions and test a recently proposed model predicting mycorrhizal fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
244
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(266 citation statements)
references
References 60 publications
18
244
0
4
Order By: Relevance
“…This foraging shift in response to perceived predation risk could explain why grasses, but not Solidago, became a carbon sink in the presence of carnivores. The higher level of fixed 13 C found in grass roots in the + carnivore treatment compared with the + herbivore treatment is consistent with the expectation that plants alter aboveground-belowground carbon allocation in response to foliar herbivory, with low levels of herbivory (i.e., the + carnivore treatment) promoting allocation belowground and higher levels (i.e., the + herbivore treatment) reducing it (15,16). This stimulation of belowground allocation with low levels of herbivory also may explain the greater 13 C retention in the + carnivore Fig.…”
Section: Discussionsupporting
confidence: 79%
“…This foraging shift in response to perceived predation risk could explain why grasses, but not Solidago, became a carbon sink in the presence of carnivores. The higher level of fixed 13 C found in grass roots in the + carnivore treatment compared with the + herbivore treatment is consistent with the expectation that plants alter aboveground-belowground carbon allocation in response to foliar herbivory, with low levels of herbivory (i.e., the + carnivore treatment) promoting allocation belowground and higher levels (i.e., the + herbivore treatment) reducing it (15,16). This stimulation of belowground allocation with low levels of herbivory also may explain the greater 13 C retention in the + carnivore Fig.…”
Section: Discussionsupporting
confidence: 79%
“…However, such studies of two-way interactions (e.g. between a plant and its herbivore or an insect herbivore and its symbionts) cannot always predict the responses of organisms in a community [7][8][9]. Here, we adopt a community approach and simultaneously examine the role of both plant -and insect -microbial interactions in modulating the plant -herbivore interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Being a polyphagous defoliator, it feeds on hundreds of host plants, including black poplars. P. nigra L. is also a host plant for native defoliators, such as Lymantria dispar L. In a scenario where losses of above-ground biomass might impact mycorrhizal response as previously reported (Gehring & Whitham 2002, Gehring & Bennett 2009), the issue is whether invasive defoliators could play a role in affecting native ecosystem components such as AM fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Over long-term, leaf herbivory (and clipping) may eventually result in reduced carbon accessibility for the host plant and fungal partners (Barto & Rillig 2010, Saravesi et al 2014, although, in spite of the re-growth of the above-ground tissue, carbon allocation to roots often increases immediately after defoliation, while allocation to shoots decreases (Dyer et al 1991, Holland et al 1996. Although the impact of leaf herbivory on colonization by mycorrhizal fungi has mainly been reported as negative, sometimes even positive or nil effects on fungal symbiosis have been detected (Gehring & Whitham 1994, 2002, Cullings et al 2001, Eom et al 2001, Hokka et al 2004, Kula et al 2005, Pietikäinen et al 2005, Walling & Zabinski 2006, Gehring & Bennett 2009, Saravesi et al 2014, Trocha et al 2015. It has been reported that the variability in responses might depend on the type and extent of defoliation, the duration of the experiment, the mycorrhizal type or plant species considered, the availability of soil nutrients or other not yet known factors (Gehring & Whitham 2002, Gehring & Bennett 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation